Factors Explaining the Integration, Identity and Sense of Belonging to Spanish Society among Youth Immigrants in Huelva - Gualda Caballero, Estrella (Migraciones Internacionales, 2017)
In this article on the social processes of integration in adolescents and youth, we describe and explain the factors which, in a representative sample of 413 immigrant adolescents in Huelva, Spain, are linked to having a sense of belonging to Spain. Approximately fi fty percent of those interviewed reported a sense of belonging to Spain, although the degree of belonging to this country was lower or non-existent in other cases. This paper attempts to delimit the elements that largely explain the degree of the sense of belonging to a country, which is crucial to understanding the processes of identifi cative integration. We found several variables linked to the sense of belonging to Spain: life satisfaction, structural opportunities perceived in Spain, orientation towards the Spanish language (monolingual or bilingual), multiple territorial identifi cation, participation in Spanish celebrations and activities, and trust in Spanish people. Factores explicativos de la integración, identidad y pertenencia a la sociedad mespañola de jóvenes inmigrantes en Huelva Resumen En este artículo, enmarcado en los procesos de integración de adolescentes y jóvenes inmigrantes, describimos y explicamos los factores que, en una muestra representativa de 413 menores inmigrantes en Huelva y provincia, se encuentran ligados al hecho de sentirse pertenecientes a España. La mitad de los entrevistados declararon sentirse parte de este país, mientras que el grado de pertenencia expresado fue intermedio o nulo en el resto de los casos. Este trabajo trata de deslindar los elementos que en mayor medida contribuyen a explicar el grado de sentimiento de pertenencia al país, siendo conscientes de la importancia que esto tiene para entender los procesos de integración identificativa. Las principales variables que se encontraron asociadas al sentimiento de pertenencia a España fueron la satisfacción con la vida, las oportunidades estructurales percibidas en este país, la orientación hacia el idioma nacional (monolingüismo y bilingüismo), una identificación territorial múltiple u orientada a España, la participación en celebraciones y actividades del país, así como la confianza hacia los españoles.